Resiprositas Dalam Ekonomi Islam, Telaah terhadap Akad Kerjasama antara induk semang dengan Pengrajin di Nagari Pandai Sikek. - zikra rahmi (IAIN Batusangkar, 2020)
this study is the unclear forms of songket weaving business cooperation between the property owner and the craftsmen in Nagari Pandai Sikek, as well as the forms of songket weaving business cooperation in terms of syari'ah economic law. The purpose of this discussion is to find out the forms of songket weaving business cooperation and how to review syari'ah economic law on these forms of songket weaving business collaboration. This type of research is field research The data collection technique uses is through interviews. Data processing is descriptive qualitative manner. The results of this research are In Islamic economics the forms of songket weaving business cooperation in Nagari Pandai Sikek are included in the ujrah contract is included which is